Linguistic framing of the Qatar blockade: a critical stylistic analysis of Al Jazeera's news reports of the Gulf crisis 2017 - Jasim, Samir A.; Abdul Jabar, Mohd Azidan; Abdul Halim, Hazlina; Jalaluddin, Ilyana (Hacettepe University, 2024)
The main objective of the current study is to carry out a critical stylistic analysis of Al Jazeera's online news reports of the 2017 Gulf crisis. The study specifically examines the linguistic strategies employed by Al Jazeera newsmakers in order to effectively communicate their ideological perspectives. The research employs Jeffries's critical stylistic framework (2010) and corpus methodologies to examine a corpus obtained from Al Jazeera English, which covers the first month of the crisis. A combination of qualitative and quantitative methodologies has been employed to analyze the ideological implications embedded within the narrative of the platform, focusing specifically on the strategies of naming, describing, equating, and contrasting. The study discloses that Al Jazeera has used specific nouns and phrases to portray the measures against Qatar as deliberate, violent, unjustifiable, and retaliatory, blaming the Saudi leadership. Complex noun phrases and evaluative adjectives have been utilized to intensify this description, while nominalization conceals agency and creates skepticism. The narrative has subtly portrayed Qatar as a passive victim of negative actions, using equating strategies to criticize the Saudi leadership's policies and the blockade. Contrasting strategies have presented contradictory actions, questioned their credibility and legitimacy, and encouraged cohesion among Gulf nations.